What will go wrong has gone wrong: asbestos exposure risk among construction workers in Nigeria. Issue 2 (3rd July 2018) - Moda, Haruna Musa; Sawyerr, Henry; Clayson, Anne
Abstract: Asbestos is a naturally occurring silicate with six varieties from two groups of minerals serpentine (chrysotile) and five amphiboles (amosite, crocidolite, tremolite, anthrophyllite and actinolite) with chrysotile widely used form. Asbestos-containing materials (ACM) use in Nigeria from 1970 to 2000 was 1, 091, 370 tons. Its demand peak coincided with landmark edifices construction in the country that include FESTAC Village and the National Theatre Iganmu. The inward low-cost housing construction investment policy in urban areas in the 1970–1980s ensured demand for ACM was consistent. Given the widespread use of ACM and non-availability of national data on workers exposure, the problem posed is unlimited. Poor implementation of asbestos regulation and industry codes of practices contributed to inadequate risk management regime. Desktop survey on ACM demand revealed the product continual use, but goes unreported. Low cost of ACMs and the absence of strong regulation to enforce a ban in the industry are critical factors in their proliferation. Lack of official record for asbestos mortality or morbidity rates and the non-existence of reliable mechanism to enforce its ban present serious health risk among construction workers. This call for national asbestos exposure survey to ascertain the extent of the problem within the construction industry.